On Modelling Migrant Behavior Driven by Imitation - Accinelli, Elvio; Carrera, Edgar J. Sánchez; Salas, Osvaldo (Journal of Reviews on Global Economics, 2014)
This paper studies the evolutionary dynamics of migration. We argue that, under bounded rationality, the strategic foundations of the migrant behavior are based in the imitation of peers. We show that any migratory flow can be modeled from a dynamical system, whose parameters reflect the social and economic policies implemented by the decision maker and the rules of the imitative process followed by the population. Education or technological innovation subsidies can lead to an increasing flow of skilled workers to the country in which this policy is more intensively developed. Impact of such subsidies on migration processes can be easily analyzed based on our model. We show that an economy may avoid skilled workers losses as a result of migration flows, only if the number of local firms investing in research and development exceeds a certain threshold value. Moreover, if this value is exceeded, such an economy is attending a positive process of imitation of skilled workers.